2021
DOI: 10.3390/metabo11090595
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Doxycycline Treatment Normalizes Levels of Some Salivary Metabolites Associated with Oral Microbiota in Patients with Primary Sjögren’s Syndrome

Abstract: Saliva is a complex oral fluid, and plays a major role in oral health. Primary Sjögren’s syndrome (pSS), as an autoimmune disease that typically causes hyposalivation. In the present study, salivary metabolites were studied from stimulated saliva samples (n = 15) of female patients with pSS in a group treated with low-dose doxycycline (LDD), saliva samples (n = 10) of non-treated female patients with pSS, and saliva samples (n = 14) of healthy age-matched females as controls. Saliva samples were analyzed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(46 reference statements)
1
5
0
2
Order By: Relevance
“…The analized A253 cells, once primed with H. Parainfluenzae exposure, induced suppression of CD4 T cell proliferation and induction of PD-L1 expression [122]. Moreover, treatment with low-dose doxycycline normalized the levels of some salivary metabolites associated with the dysbiotic microenvironment in patients with pSS to levels comparable with healthy controls [123]. These findings support the role of the microbiome on pSS pathogenesis and mucosal dysfunction.…”
Section: Oral Microbiome and Sjogren's Syndromesupporting
confidence: 54%
“…The analized A253 cells, once primed with H. Parainfluenzae exposure, induced suppression of CD4 T cell proliferation and induction of PD-L1 expression [122]. Moreover, treatment with low-dose doxycycline normalized the levels of some salivary metabolites associated with the dysbiotic microenvironment in patients with pSS to levels comparable with healthy controls [123]. These findings support the role of the microbiome on pSS pathogenesis and mucosal dysfunction.…”
Section: Oral Microbiome and Sjogren's Syndromesupporting
confidence: 54%
“…pSS is characterized by dryness of the mouth and eyes. Several previous studies have reported dysbiotic salivary microbiota in pSS patients [17][18][19][20][21][22][23]. Intestinal dysbiosis has recently been considered a possible environmental influence in pSS etiology [1][2][3]24].…”
Section: Discussionmentioning
confidence: 99%
“… Dietary sources Nutrients Associated microrganisms Ref. Micronutrients Meats, fish, and whole grains Vitamin B1 Neisseriaceae Gemellaceae Fusobacterium nucleatum [ 148–151 ] Meats, green vegetables, dairy products Vitamin B2 [ 149 , 150 ] Eggs, fish, meat, mushrooms, nuts Vitamin B3 [ 149 , 150 ] Beef, chicken, organ meats, broccoli, avocados Vitamin B5 [ 150 , 152 , 153 ] Meat, vegetables, nuts, banana Vitamin B6 [ 150 , 154 ] Leafy vegetables, peanuts, raw egg, liver, Vitamin B7 [ 150 , 155 ] Leafy vegetables, cereals, legumes, nuts and seeds Vitamin B9 [ 150 , 151 ] Fish, meat, poultry, eggs, and dairy products Vitamin B12 [ 150 , 156 ] Green vegetables (kale, spinach, cabbage, lettuces), egg yolk Vitamin K Not identified [ 157 ] Fish eggs, liver, mushrooms, milk Vitamin D Fusobacterium nucleatum, Porphyromonas gin...…”
Section: Potential Role Of MD In Modulating Oral Microbiome In Oral D...mentioning
confidence: 99%